Bicyclic β‐Sheet Mimetics that Target the Transcriptional Coactivator β‐Catenin and Inhibit Wnt Signaling. (5th May 2021) - Wendt, Mathias; Bellavita, Rosa; Gerber, Alan; Efrém, Nina‐Louisa; van Ramshorst, Thirza; Pearce, Nicholas M.; Davey, Paul R. J.; Everard, Isabel; Vazquez‐Chantada, Mercedes; Chiarparin, Elisabetta; Grieco, Paolo; Hennig, Sven; et al.
Abstract: Protein complexes are defined by the three‐dimensional structure of participating binding partners. Knowledge about these structures can facilitate the design of peptidomimetics which have been applied for example, as inhibitors of protein–protein interactions (PPIs). Even though β‐sheets participate widely in PPIs, they have only rarely served as the basis for peptidomimetic PPI inhibitors, in particular when addressing intracellular targets. Here, we present the structure‐based design of β‐sheet mimetics targeting the intracellular protein β‐catenin, a central component of the Wnt signaling pathway. Based on a protein binding partner of β‐catenin, a macrocyclic peptide was designed and its crystal structure in complex with β‐catenin obtained. Using this structure, we designed a library of bicyclic β‐sheet mimetics employing a late‐stage diversification strategy. Several mimetics were identified that compete with transcription factor binding to β‐catenin and inhibit Wnt signaling in cells. The presented design strategy can support the development of inhibitors for other β‐sheet‐mediated PPIs. Abstract : Starting from a 52 amino acid protein binding epitope, a bicyclic β‐hairpin structure was developed to bind the transcriptional coactivator β‐catenin. Our structure‐based design approach was supported by screening a focused library of bicyclic mimetics which was generated via late‐stage diversification. The most active bicyclic β‐hairpin shows cell‐penetration and inhibits Wnt signaling in a cell‐based assay.